Implementation of Minister of Finance Regulation Number PMK 131/PMK/2024 at the Jakarta Setiabudi Dua Tax Office: A George Edward Iii Model Perspective - PUTRIARA , Nisa Arifah; SUPRIYADI, Supriyadi (Journal of Governance, Taxation and Auditing, 2025)
This study aims to analyze the implementation process, challenges, and strategies of the enforcement of Minister of Finance Regulation Number 131/PMK/2024 at KPP Pratama Jakarta Setiabudi Dua. The theoretical framework employed is George Edward III’s model of public policy implementation, which includes the variables of communication, resources, disposition, and bureaucratic structure. This research adopts a qualitative method with deductive thematic analysis techniques. Primary data were collected through in-depth interviews with officers from KPP Pratama Jakarta Setiabudi Dua, officials from the Directorate General of Taxes (DJP) Head Office, tax practitioners, and academics. Secondary data were obtained from policy documents, institutional reports, and academic literature. The findings reveal that, in general, the implementation of the regulation has been fairly effective, although several significant challenges remain, including limited time for information dissemination, heterogeneity in public tax literacy levels, instability of the Core Tax Administration System (CTAS), and staff competency issues. To address these challenges, identified strategies include implementing more massive and segmented socialization, developing a public communication strategy, producing educational content on social media, implementing a pilot project on certain Coretax modules, utilizing legacy applications as a transitional solution in the administrative process, and staff training.